PENGARUH PEMAHAMAN LITERASI KEUANGAN DAN PENGGUNAAN PAYLATER TERHADAP PERILAKU IMPULSIVE BUYING BAGI PENGGUNA E-COMMERCE DI KALANGAN GENERASI Z - Putri, Natasha; Wany, Eva; Malludin (Ekomania, 2024)
This research aims to analyze the impact of the Using paylater as a payment method can change people's lifestyles, especially among generation Z who were born in 1995-2010. Paylater payment method offers can attract generation Z who basically have an understanding in the latest technology. Besides that, the majority of generation Z still do not have an income. However, they have a high desire to shop using PayLater. It is not impossible for generation Z to be able to use paylater wisely, but most of them have difficulty managing paylater bills. Therefore, the aim of this research is to review the influence of financial literacy and the use of paylaters on impulsive buying behavior among generation Z. By using 50 generation Z respondents at the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya, the results showed that financial literacy and impulsive buying behavior has a significant influence among generation Z. Meanwhile, the use of paylater has no effect on impulsive buying behavior among generation Z.